Ritus Metoh-Tohan Pada Masyarakat Desa Manikliyu, Kecamatan Kintamani, Kabupaten Bangli - Ayu Ratna Dewi, Ni Made; ., Purwadi; Suwena, I Wayan (Humanis; Vol 21 No 1 (2017)DO - 10.24843/JH.2017.v21.i01.p12, 2017)
Manikliyu society , Kintamani has a rites that is performed from generation to generation that is metoh-tohan. The problem in this research, focuses on two things: (a) how is the process of metoh-tohan rites in Manikliyu Village and (b) what is the function and meaning of metoh-tohan implementation in Manikliyu Village. As for its purpose is to know the procession of metoh-tohan rite s , and to reveal the function and meaning of the implementation of metoh-tohan rites in Manikliyu Village. The concept used as a guideline in this research is the concept of rite s , metoh-tohan, and Bali Aga Village. Similarly, in this study using the method of ethnography in the form of qualitative research with data collection techniques through participatory observation, in-depth interviews, and literature study. The results showed that the ritesl metoh-tohan through various stages: nanceb (install) penjor, making temple Bentar and Gelung Kuri, Melasti, Sampiyan Oyod lunga (visiting) to Kahyangan Tiga, Pura Dadia, and pengaksan, metoh-tohan, Metalun Teruna, Metani, Metalun Desa, and Mabuang. The Function and meaning of rit es metoh-tohan as follows: (a) function and social meaning,(b) function and meaning of education,(c) Economic function, (d) the function meaning of religious, and (e) psychological function.